1500m hack research findings - van Musschenbroek, M. (1999)
I would suspect by now that everyone is heavily into their summer training programs, building up their conditioning, in the comfort of the heat. Have any of you noticed that after a hard workout you rarely cough up the amounts of phlegm that are so prevalent during the winter months. Have you ever wondered why, or did you always think you were catching a cold? A group of researchers set out to find out if there was a reason. Three doctors from the Netherlands set up an experiment to examine, what is called, the Bronchoconstrictor effect, (chest tightness, excess mucous etc.) in colder weather or better know as the 1500 Hack! Taking note of the Peak Expecting Flow (P.E.F.) during everyday situations and recording differences after competitions. (The details of the study by Paul, Bogaard and Hop were published in the International Journal of Sports Medicine Vol. 14 1993) They had two study groups to work with. The first was the Dutch National Speed Skating team, training in Calgary, average age 22.7 yrs. The second group was a local team, average age 14.6 yrs. from Utrecht, Holland. Using a device called the Mini Wright Peak Flow Meter the skaters recorded the reading at specified times of the day. This instrument measures the airway resistance in your lungs. In order to see what effect stressful situations would leave on the lungs the skaters agreed to use the meter immediately following, and at preset times following, a 1500m race. Having compiled all this information, the study hypothesized that there is, in fact, a reaction that occurs. (See Fig. 1 re: Peak Expiratory Flow Data) It was concluded in the study that the colder and dryer the air was, it increased the stimulation of the vagal nerve activity, which increases the production of mucous (heaviness) in addition to creating a Bronchoconstrictor effect (tightness of the lungs). These two circumstances trigger a coughing reaction. The cough tends to last several hours peaking approximately 90 minutes following the race. This is a normal reaction even though it sounds terrible to listen to. So when you start hacking (coughing) after a race, relax, it is just your body taking care of itself. It will pass.